Sorafenib-associated hand-foot skin reaction: practical advice on diagnosis, mechanism, prevention, and management. Issue 12 (2nd December 2019) - Ai, Leilei; Xu, Ziheng; Yang, Bo; He, Qiaojun; Luo, Peihua
ABSTRACT: Introduction : Sorafenib is a multitargeted tyrosine kinase inhibitor, which has been mainly used in the treatment of advanced hepatocellular carcinoma and renal cancer. However, hand-foot skin reaction (HFSR), as one of the most common adverse reactions, have hindered its long-term clinical application. At present, the mechanism of its occurrence has not been clearly studied and it leads to the lack of effective means of intervention. This article reviews known mechanism and management methods of HFSR caused by sorafenib. Areas covered : The author reviews HFSR caused by the treatment of sorafenib including the mechanism and management. English language reports located through PubMed are reviewed. Expert opinion : There are some conjectures about the mechanism of HFSR. However, the mechanism of HFSR induced by sorafenib is still unclear at present. In the absence of understanding the mechanism of HFSR, the most common method for clinical treatment of sorafenib-induced HFSR is dose down-regulation or discontinuation of treatment, which affects efficacy and even survival. Future research should focus on the mechanism of HFSR to find out new ways for prevention. Precautionary measures before the occurrence of HFSR can also be studied in the future.